2010
DOI: 10.4140/tcp.n.2010.440
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Alzheimer's Disease: Is There a Link?

Abstract: The current observational studies seem to identify a link between vitamin D and dementia, particularly AD. Before this evidence can be used to make a recommendation for routine supplementation in elderly patients to prevent AD, more prospective trials with a longer follow-up period are needed to show a causality relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 31 publications
1
18
0
2
Order By: Relevance
“…There are several lines of evidence that an increase in extracellular actin in the CSF, vitamin D deficiency, neuroendothelial disruption, and immune dysfunction are commonly associated with AD pathology. [42][43][44][45] Interestingly, DBP is known to act as an actin scavenger, a vitamin D transporter, a growth factor for endothelial cells, an immunmodulator, and a macrophage activator. 10,46 Therefore, it is possible that DBP may improve the synaptic loss and inhibit memory deficits through the regulation of other pathological mediators of AD.…”
Section: Discussionmentioning
confidence: 99%
“…There are several lines of evidence that an increase in extracellular actin in the CSF, vitamin D deficiency, neuroendothelial disruption, and immune dysfunction are commonly associated with AD pathology. [42][43][44][45] Interestingly, DBP is known to act as an actin scavenger, a vitamin D transporter, a growth factor for endothelial cells, an immunmodulator, and a macrophage activator. 10,46 Therefore, it is possible that DBP may improve the synaptic loss and inhibit memory deficits through the regulation of other pathological mediators of AD.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested a link between vitamin D deficiency and cognitive impairment and dementia, particularly in the elderly (8,9). Vitamin D, also known as calciferol, is a steroid hormone that can be obtained from dietary sources as both vitamin D2 and D3.…”
Section: Introductionmentioning
confidence: 99%
“…LOAD is a complex disorder, caused by a combination of genetic and environmental risk factors, all of which alter risk for AD without alone being necessary or sufficient for the development of the disorder. Age is the most significant environmental risk factor for LOAD, and other factors which have been implicated in increasing or decreasing LOAD risk, affecting age of onset, or affecting disease progression include educational status, head injury, hypertension, high cholesterol and vitamin intake (Dosunmu et al 2007;Pogge 2010). …”
Section: Late Onset Admentioning
confidence: 99%
“…Age is by far the most significant environmental risk factor for late onset AD, with risk increasing dramatically as aging occurs. Other factors include educational status, head injury, exercise, hypertension, and vitamin intake (Dosunmu et al 2007;Dangour et al 2010;Pogge 2010), although what effect modifications of these risk exposures could have on public health remains to be determined (Dangour et al 2010). …”
Section: Preventionmentioning
confidence: 99%